Use of Connected Technologies to Assess Barriers and Stressors for Age and Disability-Friendly Communities - Zanwar, Preeti; Kim, Jinwoo; Kim, Jaeyoon; Manser, Michael; Ham, Youngjib; Chaspari, Theodora; Ahn, Changbum Ryan (Frontiers in Public Health, 2021)
Background: The benefits of engaging in outdoor physical activity for older adults are numerous. However, previous work related to the outdoor monitoring of physical activities did not sufficiently identify how older adults respond to diverse elements of urban built environments, including structural characteristics, safety attributes, and aesthetics. Objective: To synthesize current multidisciplinary tends on the use of connected technologies to mitigate environmental barriers and stressors among older adults and those with disabilities. Methods: A multidisciplinary overview and synthesis of literature. Results: First, we provide a review of measurement and monitoring of outdoor physical activity in community environments and during transport using wearable sensing technologies, their contextualization and using smartphone-based applications. We describe physiological responses (e.g. gait patterns, electrodermal activity, brain activity, heart rate), stressors and physical barriers during outdoor physical activity. Second, we review the use of visual data (e.g. Google street images, Street score) and machine learning algorithms to assess physical (e.g. walkability) and emotional stressors (e.g. stress) in community environments and their impact on human perception. Third, we provide a review of the use and challenges of smartphone-based software driving behavior real-time data and the potential for such data to be confounded by environmental signals in older adults. Lastly, we provide alternative modes of transport besides for older adults and for those with disabilities. Conclusion: Environmental design for connected technologies and interventions to promote mobility, and to reduce barriers and stressors for community dwelling older adults and those with disabilities, likely requires a connected city for age-friendly communities.